PERANCANGAN RUANG PARKIR DI KAWASAN RUMAH SAKIT JALAN SAMUDERA KOTA LHOKSEUMAWE - Hafiez, Muhammad; Suryani, Fitrika Mita; Mutiawati, Cut; Faisal, Ruhdi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2023)
Kesrem General Hospital and PMI Hospital are public service facilities in Lhokseumawe City. The parking area for the Kesrem General Hospital and PMI cannot accommodate all vehicles so vehicle users must park their vehicles on the road which results in congestion in front of the hospital. Therefore this study aims to design parking space requirements. The method used is the method based on the largest difference between the arrival and departure of vehicles according to the Guidelines for Planning and Operation of Parking Facilities at the Directorate General of Land Transportation 1998. Observations start from 08.00 WIB to 17.00 WIB for 3 days, namely Monday, Tuesday and Thursday, namely the 8th, 9 and 11 August 2022. The results of the analysis show that the parking area for motorbikes can still accommodate parking requests because the available land area is 271.5 m², while the required land area is only 222.63 m². The car parking area is no longer able to accommodate the demand. This can be seen from the calculation results that the required area is 300 m², while the available area is only 212.5 m². The parking pattern for motorcycle parking areas is island parking pattern with an angle of 90°, for car parking areas a one-sided parking pattern and two-sided parking patterns are used with an angle of 90°, and for car parking areas on the road using a one-sided parking pattern with an angle of 60°.